Anti-oxidative and Anti-apoptotic Effects of Acupuncture: Role of Thioredoxin-1 in the Hippocampus of Vascular Dementia Rats. (21st May 2018) - Zhu, Wen; Wang, Xue-Rui; Du, Si-Qi; Yan, Chao-Qun; Yang, Na-Na; Lin, Lu-Lu; Shi, Guang-Xia; Liu, Cun-Zhi
Graphical abstract: Highlights: The expressions of Trx-1 and TrxR-1 were decreased in the hippocampus in VD rats. Acupuncture ameliorated cognitive impairment and hippocampal neuronal damage. Acupuncture up-regulated the hippocampal Trx-1 and TrxR-1 and inhibited the ASK1-JNK/p38 pathway. Trx-1siRNA blocked the beneficial effects induced by acupuncture. Abstract: Emerging evidence suggests that acupuncture treatment has anti-oxidative effects that affect cognitive impairment in vascular dementia (VD) rats. In the present study, we aimed to investigate whether thioredoxin-1 (Trx-1)/thioredoxin reductase-1 (TrxR-1) was involved in the beneficial effects of acupuncture. After 2-weeks of acupuncture treatment, Morris water maze (MWM), dihydroethidium (DHE) staining, Nissl staining and TdT-mediated dUTP nick end labeling (TUNEL) staining were used to assess the effects of acupuncture on cognitive function and hippocampal neuronal injury in two-vessel occlusion (2VO) model. The protein and mRNA levels of Trx-1 and TrxR-1, the activity of TrxR-1 as well as the phosphorylation of the apoptosis signal-regulating kinase 1 (ASK1)-c-Jun N-terminal kinase (JNK)/p38 pathway were measured by Western blot, real-time PCR analysis, TrxR-1 activity analysis and immunofluorescence (IF) staining respectively. We found that there were oxidative and apoptotic injury in the CA1 area, accompanied with the decreased expressions of Trx-1 and TrxR-1 in the hippocampus. Acupuncture ameliorated cognitive deficits caused by cerebral ischemic injury and inhibited oxidative stress and neuronal apoptotic injury in the hippocampus. Acupuncture also up-regulated the expressions of Trx-1 and TrxR-1, increased the activity of TrxR-1, accompanied with inhibiting the activation of the ASK1-JNK/p38 pathway. However, the effects of acupuncture on improving cognitive function, inhibiting oxidative stress and neuron apoptotic damage were blocked by Trx-1siRNA. In conclusion, these findings indicated that acupuncture treatment improved VD though anti-oxidative and anti-apoptotic mechanisms which involved the up-regulations of Trx-1/TrxR-1 and inhibitions of ASK1-JNK/p38 pathway.